Cost-utility analysis of searching electronic health records and cascade testing to identify and diagnose familial hypercholesterolaemia in England and Wales - Crosland, Paul; Maconachie, Ross; Buckner, Sara; McGuire, Hugh; Humphries, Steve E.; Qureshi, Nadeem (Elsevier, 2018)
Background and aims: The cost effectiveness of cascade testing for familial hypercholesterolaemia (FH) is well recognised. Less clear is the cost effectiveness of FH screening when it includes case identification strategies that incorporate routinely available data from primary and secondary care electronic health records.